Classical homocystinuria presenting with bilateral ectopia lentis and multisystem involvement in a pediatric patient: a case report - Abhinay, Elagandula; Rathoria, Ekansh; Priyanka, Goud; Vishnoi, Dakshata; Lahari, Rohitash; Yadav, Suresh Kumar; Srivastava, Akash; Priyadarshini, Prerna (International Journal of Research in Medical Sciences, 2025)
Homocystinuria (HCU) is an uncommon inherited metabolic condition caused by a deficiency of the enzyme cystathionine beta-synthase (CBS), which disrupts the normal breakdown of methionine. It leads to elevated homocysteine levels and a wide spectrum of multisystem clinical manifestations. Early recognition and intervention are crucial to prevent irreversible complications. We report the case of a 10-year-old male, firstborn of non-consanguineous parents, presenting with progressive visual impairment, generalized weakness, bilateral knee swelling and increased urinary frequency. Family history revealed early vision loss in a younger sibling. Ocular examination showed bilateral ectopia lentis and optic atrophy. Skeletal features were suggestive of a Marfanoid habitus. Cognitive evaluation indicated borderline intellectual functioning. Laboratory investigations revealed macrocytic anemia, mild liver enzyme elevation and a significantly elevated serum homocysteine level (50 µmol/l), confirming the diagnosis of classical homocystinuria. High-dose pyridoxine and folate supplementation were initiated. This case highlights the classical phenotype of homocystinuria, including ocular, skeletal, hematologic, hepatic and cognitive involvement. Despite the treatable nature of HCU, diagnostic delays remain common, especially in resource-limited settings. Early diagnosis through clinical suspicion and biochemical testing, along with multidisciplinary management, is essential to reduce morbidity. Homocystinuria should be considered in pediatric patients presenting with ectopia lentis, skeletal disproportions and developmental delay. Timely diagnosis and appropriate treatment can significantly improve outcomes and prevent life-threatening complications.